McCarthy Day flyer (1968)
This flyer advertises "McCarthy Day" at the Hollywood Palladium on August 15 at 7:30 p.m., where Senator Eugene McCarthy would address supporters via closed-circuit television from New York. The event, organized by the McCarthy for President Campaign Committee, aimed to demonstrate public support for McCarthy to convention delegates and featured appearances by prominent actors, musicians, and speakers including Paul Newman and Dolores Huerta. The program included entertainment, music, and an art exhibit, with tickets available for a $3.00 donation.